Technology Enhanced Health and Social Care for Vulnerable People During the COVID-19 Outbreak - Romanopoulou, Evangelia D.; Zilidou, Vasiliki I.; Gilou, Sotiria; Dratsiou, Ioanna; Varella, Annita; Petronikolou, Vasileia; Katsouli, Aikaterini-Marina; Karagianni, Maria; Bamidis, Panagiotis D. (Frontiers in Human Neuroscience, 2021)
The COVID-19 pandemic has spread rapidly worldwide with critical consequences in health, as well as in social, economic, and particularly in psychological conditions of vulnerable people, especially older adults. Therefore, it is necessary the direct attention to their health care needs and related interventions. Information and Communication Technology (ICT) have direct impact on older adults’ health and quality of life leading to decreased depression and loneliness, along with empowerment of independent life. Many studies involve cognitive training programs/software based on new technological systems that provide to vulnerable people access to gamified, attractive, cognitive exercises for overall functionality everywhere and at any time. Twenty-four participants (mean age 69.3 years) were assigned to this study. Τhe cognitive training component of LLM Care was used as an interactive software to enhance participants’ cognitive functions. The intervention lasted 12 weeks with the frequency of 2-4 times per week in sessions of at least 30 minutes. Participants used their personal devices (tablets/laptops) in their own residence, while technical and consulting guidance was provided by LLM Care certified trainers. They were informed about the purpose of the study, while consent forms along with psychological assessments were distributed every two weeks to periodically evaluate their psychosocial and mental health conditions. The assessments included the World Health Organisation-Five Well-Being Index (WHO-5), the Short Anxiety Screening Test (SAST), the System Usability Scale (SUS) and the Impact Factor Event Scale (IES-R). According to the results, the participants with improved well-being tended to report decreased subjective distress caused by COVID-19, and their engagement with new technologies can potentially minimize the negative outcomes occurred by the current stressful situation, mitigating the effect of hyperarousal symptoms, while increasing their overall well-being. Well-being seems to remain relatively stable among older adults and decreases only when adversities occur, while the usability of the software was perceived as marginally acceptable by participants. The exploitation of the LLM Care contributes to the improvement of older adults’ well-being and alleviates the negative experience caused by stressful situations like COVID-19.